Tingkat Kompetensi TIK Guru PAUD di Era Abad 21 - Nuraeni, Cucu; Anjani, Ratna; Nabila, Siti Winda Mariam (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2025)
ICT competency framework, Knowlage Deepenin, ICT competency of early childhood teachers In the 21st century, the role of information and communication technology (ICT) in education has become increasingly crucial. Teachers are required to be able to integrate ICT into the teaching and learning process to improve the quality of learning. This study aims to examine the level of ICT competence of early childhood education (PAUD) teachers in TK Ashabul Fikri. Based on the UNESCO ICT Competency Framework for Teachers (ICT CFT), teacher ICT competence is classified into three levels: technology literacy (knowlage acquisition), knowledge deepening, and knowledge creation. The results of the study show that the ICT competence of teachers in TK Ashabul Fikri is at the Knowledge Deepening (knowladge deepening) level, where teachers have implemented ICT in learning but have not yet been able to create ICT-based innovations.